2023
DOI: 10.1101/2023.10.30.564810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Charting the transcriptomic landscape of primary and metastatic cancers in relation to their origin and target normal tissues

Neel Sanghvi,
Camilo Calvo-Alcañiz,
Padma S. Rajagopal
et al.

Abstract: SUMMARYMetastasis is a leading cause of cancer-related deaths, yet understanding how metastatic tumors adapt from their origin to target tissues is challenging. To address this, we assessed whether primary and metastatic tumors resemble their tissue of origin or target tissue in terms of gene expression. We analyzed gene expression profiles from various cancer types, including single-cell and bulk RNA-seq data, in both paired and unpaired primary and metastatic patient cohorts. We quantified the transcriptomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Site-specific archetype adaptation may present a novel therapeutic vulnerability in metastatic cancers. Consistent with our findings, prior studies indicate that metastatic tumors express genes associated with their target tissues [26,50]. Thus, the dual role of archetypes as markers for such tissue-specific gene expression patterns and predictors of tumor drug sensitivities suggests that site-specific archetype enrichment patterns may highlight vulnerabilities in metastatic tumors to treatments associated with the archetypes of their destination tissues.…”
Section: Normal Tissue Signature Enrichment Influences Pan-cancer Dru...supporting
confidence: 89%
“…Site-specific archetype adaptation may present a novel therapeutic vulnerability in metastatic cancers. Consistent with our findings, prior studies indicate that metastatic tumors express genes associated with their target tissues [26,50]. Thus, the dual role of archetypes as markers for such tissue-specific gene expression patterns and predictors of tumor drug sensitivities suggests that site-specific archetype enrichment patterns may highlight vulnerabilities in metastatic tumors to treatments associated with the archetypes of their destination tissues.…”
Section: Normal Tissue Signature Enrichment Influences Pan-cancer Dru...supporting
confidence: 89%
“…Modeling the molecular development of BC in canine mammary tumors revealed that lipid metabolic processes were significantly enriched in BC progression expression patterns and in mammary carcinomas [ 71 ]. Additionally, recent evidence found enhanced expression of bile acid metabolism in a subset of breast and colon liver metastasis [ 72 ].…”
Section: Discussionmentioning
confidence: 99%